Procalcitonin as an antibiotic stewardship tool in COVID-19 patients in the intensive care unit (2020)
The coronavirus-2019 (COVID-19) pandemic caused by the virus SARS-CoV-2 infection has imposed significant demand on all healthcare systems. Based on national and international guidance which were mostly anecdotal [1], COVID-19 patients admitted to our General Intensive Care Unit (GICU) were routinely commenced on antibiotics to cover possible secondary bacterial lower respiratory tract infection (LRTI). The antibiotics should have been reviewed after 48 h, however, it was challenging to stop early because of the many factors such as persistent hyperinflammatory status, ongoing/worsening lung infiltrates with the need for continued mechanical ventilation, and also partly because of the lack of reliable indicators of bacterial infection.